Formulation and Evaluation of Piroxicam and Aceclofenac Tablets Employing Prosolve by Direct Compression Method - CHOWDARY, K.P.R.; TRIPURA SUNDARI, P.; SURYA PRAKASA RAO, K. (Asian Journal of Chemistry, 2010)
Prosolve, a new directly compressible vehicle consists of microcrystalline cellulose (98 %) and colloidal silicon dioxide (2 %). Piroxicam (20 mg) and aceclofenac (100 mg) tablets were formulated employing prosolve and three disintegrants namely potato starch, primogel and croscarmellose sodium by direct compression method with a view to enhance their dissolution rate. In the micromeritic evaluation prosolve and its blends with other tablet ingredients exhibited excellent to good flow needed for direct compression. All the tablets formulated employing prosolve fulfilled the official (IP) and GMP standards with regard to various tablet characters. These tablets also gave 2 to 5 fold increase in the dissolution rate when compared to commercial tablets. Among the three disintegrants primogel gave higher dissolution rates with both piroxicam and aceclofenac.